Intertekstualitas Tafsir: Mengungkap Keterpengaruhan Anwār at-Tanzīl terhadap Al-Kasysyāf dalam Pemaknaan Kata Auliya - Fauzi, Muhammad (Contemporary Quran, 2022)
The interpretation of the word auliya in Islamic exegesis is a significant issue because it is linked to concepts of loyalty, friendship, and leadership within a religious framework. The classical tafsir works, Anwar at-Tanzil and al-Kasysyāf, provide differing perspectives on the meaning of auliya. This article seeks to bridge this gap by examining the interpretation of auliya in Anwar at-Tanzil and al-Kasysyāf and tracing the influence of one upon the other using Julia Kristeva's intertextuality approach. Employing a thematic method, this study focuses specifically on the meaning of auliyaas its primary subject of analysis. The findings reveal that al-Baiḍawī's interpretation of auliya is heavily influenced by the earlier interpretation found in al-Kasysyāf. Through Kristeva's intertextuality framework, it becomes evident that the principles of parallelism, modification, and expansion or haplology play a dominant role in this influence. The prevalence of these principles points to a tendency towards transposition as an ideologeme, marked by the inclusion of elements of addition, subtraction, adjustment, and the reorganization of ideas in al-Baiḍawī's interpretation of auliya.